A numerical method for double-plated structure completely filled with liquid subjected to underwater explosion. (May 2017) - Liu, Guo-zhen; Liu, Jian-hu; Wang, Jun; Pan, Jian-qiang; Mao, Hai-bin
Abstract: The double-plated structure is extensively applied to the surface ships and submarines. Between the two plates there always exists liquid such as water or oil. When it is exposed to the attack by underwater weapon, the shock wave firstly hits the outer plates, and then it is transmitted into the internal liquid, subsequently to the inner plates. The mechanism in this process is so complex that has been a troublesome problem for a long time. In this paper, a numerical method is developed to solve this problem. The second-order doubly asymptotic approximations (DAA) is used to analyze the external fluid-structure interaction (FSI) effect for the outer fluid field with the outer plates, and cavitating acoustic finite element (CAFE) is used to model the internal FSI effect. Results obtained by this approach show good agreement with results of the excitation problem of 3D fluid-filled shell by a plane step wave. Last, two experiments are implemented to validate the method. From the comparative results, it shows that the simulation results coincide well with tests. Highlights: A numerical method is developed to solve double-plated structure completely filled with liquid under UNDEX. The DAA's is used to analyze the external FSI effect and CAFE element is used to model the internal FSI effect. Theoretical and test examples are given to verify the numerical method. The computation results coincide well with them. The method would make up the gap of solving underwater multi-physical coupling problems based on the family of DAA's.